Phytochemicals in Inhibition of Prostate Cancer: Evidence from Molecular Mechanisms Studies - Qiongyu Hao; Yanyuan Wu; Jaydutt V. Vadgama; Piwen Wang (Biomolecules, 2022)
Prostate cancer is one of the leading causes of death for men worldwide. The development of resistance, toxicity, and side effects of conventional therapies have made prostate cancer treatment become more intensive and aggressive. Many phytochemicals isolated from plants have shown to be tumor cytotoxic. In vitro laboratory studies have revealed that natural compounds can affect cancer cell proliferation by modulating many crucial cellular signaling pathways frequently dysregulated in prostate cancer. A multitude of natural compounds have been found to induce cell cycle arrest, promote apoptosis, inhibit cancer cell growth, and suppress angiogenesis. In addition, combinatorial use of natural compounds with hormone and/or chemotherapeutic drugs seems to be a promising strategy to enhance the therapeutic effect in a less toxic manner, as suggested by pre-clinical studies. In this context, we systematically reviewed the currently available literature of naturally occurring compounds isolated from vegetables, fruits, teas, and herbs, with their relevant mechanisms of action in prostate cancer. As there is increasing data on how phytochemicals interfere with diverse molecular pathways in prostate cancer, this review discusses and emphasizes the implicated molecular pathways of cell proliferation, cell cycle control, apoptosis, and autophagy as important processes that control tumor angiogenesis, invasion, and metastasis. In conclusion, the elucidation of the natural compounds’ chemical structure-based anti-cancer mechanisms will facilitate drug development and the optimization of drug combinations. Phytochemicals, as anti-cancer agents in the treatment of prostate cancer, can have significant health benefits for humans.